The Effect Of Yoga Exercise On Reducing Pain Scale Of Joints In The Elderly In The Inpatient Room Of Hospital X (Comprehensive Health Care, 2024)
Background: The problem of joint disease is a disorder of the joints that causes joint pain. Objective: To be able to understand, explain and apply evidence-based practice in professional nursing, after carrying out an analysis of evidence-based practice. The effect of yoga exercises on reducing the scale of joint pain in the elderly in the ward. inpatient Hospital X Method: The evidence base nurse (EBN) design used was the Quasy Experiment, especially the pretest-posttest design. Namely by conducting observations before and after the intervention without a control group. There were two intervention groups, namely the group given yoga exercise therapy and swallowing exercises for 6 consecutive days times a day. Results: The results of the distribution of yoga exercise results on reducing joint pain in elderly patients after doing yoga exercises with a mean value of 1.25 (SD=0.500) while a decrease in joint pain in elderly patients in the control group with a mean value of 1.75 (SD=0.500) with p-value (0.564) or greater than the significance value of p-value >0.05 Conclusion: which means there is no difference in the effect of yoga exercise on reducing joint pain in patients in the intervention group and control group in this study. Painful Keywords: Elderly, Joint Pain, Yoga Exercise